Factors influencing the intention to use monthly tax deduction as final tax among employees in Bangi, Malaysia - Othman, Syaiful Izam (2020)
In Malaysia, the implementation of the Monthly Tax Deduction (MTD) as a final tax scheme was introduced in 2014 to employment income taxpayers. After six years of implementation, the number of salaried taxpayers who choose this scheme is minimal, although it provides benefits, especially in terms of time-saving and costs. Thus, the purpose of this study is to examine taxpayers’ intention to use MTD as final tax from the perspective of the Theory of Planned Behaviour (TPB). This study provides empirical evidence on the factors affecting taxpayers’ intention to use MTD as final tax. The study extends the TPB model by dividing perceived behavioural control (PBC) into two dimensions i.e., Knowledge and Awareness. The results of this study indicate that attitude, subjective norms, and one dimension of PBC i.e., awareness, have a positive influence on intention to use MTD as final tax; while knowledge is found to be insignificant. Using a self-administered questionnaire, 175 useable responses were collected from salaried earners who filed their 2019 Income Tax Return Form (ITRF) at the Inland Revenue Board Malaysia (IRBM) Bangi Branch. All the hypotheses were tested using multiple regression analysis. Results show that 77.9% of the variance in intention to use MTD as final tax is explained by attitude, subjective norms, knowledge and awareness. This study confirms the applicability of TPB in the intention to use MTD as final tax setting. These findings would assist the IRBM in formulating strategies or mechanisms for improvement using MTD as final tax.